Dramaturgy: from text to scene, from action to meaning (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article aims to address the definition of dramaturgy. To do so, it focuses on the detachment of the term from the notion of “written text”, and on the explosion of meanings of this concept from the second half of the 20th century. The understanding of this definition will be built from a historical and critical review of the reference literature, articles and academic texts, both by national and foreign authors. In its first part, the article focuses specifically on the theatrical origin of the notion of dramaturgy; then, it deals with the expansion of dramaturgy to other areas, focusing mainly on contemporary dance; and ends by dealing with the notion of dramaturgy as structuring the meaning of the play, based on Ana Pais.
Keywords: dramaturgy; dance dramaturgy; Marianne Van Kerkhoven; Ana Pais